Foamed geopolymer: The relationship between rheological properties of geopolymer paste and pore-formation mechanism. (20th December 2020) - Gu, Gonghui; Xu, Fang; Huang, Xiaoming; Ruan, Shaoqin; Peng, Chao; Lin, Juntao
Abstract: The movement of precast foams in geopolymer paste was mainly controlled by the rheological properties of geopolymer paste, influencing the foaming process and the corresponding final performance of foamed geopolymer. In this study, the precast foams were first produced via a physical approach and then were mixed with geopolymer paste to prepare the foamed geopolymer with different amounts of water incorporation, and several physical and microscopic properties of the prepared specimens were also studied. In view of the mechanical performance, this study clarified the relationship between the rheological properties of geopolymer paste and the foam migration, facilitated by the force model of the single precast foam in geopolymer paste, and the significance of rheological properties on the formation process of pore structures within geopolymer paste was also highlighted, where the foaming process was mainly controlled by four types of external forces, and the forces were related with the rheology of geopolymer paste. Finally, the laws of migration and variation associated with precast foams under different external force systems and pore-formation mechanism were also revealed. Highlights: The rheological behaviors of paste and the toughness of precast foam were quantitatively characterized;. The relationship between rheological properties of paste and pore-formation mechanism was analyzed. The force model of the single foam in the foamed geopolymer was established;. The migration and variation law of precast foam systems in the paste were revealed.